Determination of uranium in fishes samples from selected regions in Iraq using neutron activation technique for nuclear track detectors - Anees A. Hassan (Al-Qadisiyah Journal of Pure Science, 2018)
To establish a base line against which future pollution may be measured, six common commercial species of Iraqi river fish were analysed for uranium content. The fishes studied were: Barbus luteus, Barbus sharpeyi, Aspius heckle, Barbus heckle, Pampus argentues and Pilchard. The fish samples were collected from two key governorates namely, Basrah (southern Iraq) and Babil (central Iraq). Uranium concentration in fishes samples was measured by using fission tracks registration in CR-39 detector that caused by the bombardment of (U235) with thermal neutrons from (Am-Be) neutron source. The results show that the uranium concentrations in fish samples ranged from 1.78 Â± 0.19 Î¼g kg-1 to 8.31 Â± 0.51 Î¼g kg-1. The results indicated that the mean value of uranium concentration in fish samples of Basrah governorate is higher than those of Babil governorate.